MiR-1301-3p Inhibits Epithelial-Mesenchymal Transition via Targeting RhoA in Pancreatic Cancer. (26th February 2022) - Zhang, Xinxue; Ren, Zhangyong; Xu, Junming; Chen, Qing; Ma, Jun; Liu, Zhe; Kou, Jiantao; Zhao, Xin; Lang, Ren; He, Qiang
Abstract : Micro(mi)RNAs play an essential role in the epithelial-mesenchymal transition (EMT) process in human cancers. This study aimed to uncover the regulatory mechanism of miR-1301-3p on EMT in pancreatic cancer (PC). The miRNA profilings from Gene Expression Omnibus data sets (GSE31568, GSE41372, and GSE32688) demonstrated the downregulation of miR-1301-3p in PC tissues, which was validated with 72 paired PC tissue samples through qRT-PCR detection. The low level of miR-1301-3p was associated with a poor prognosis for PC patients from the PC cohort of The Cancer Genome Atlas and the validation cohort. Gene Ontology analyses indicated that the target genes of miR-1301-3p were involved in cell cycle and adherent junction regulation. In vitro assays revealed that miR-1301-3p suppressed the proliferation and migration abilities of PC cells. Western blotting and luciferase reporter assays suggested that miR-1301-3p inhibited RhoA expression by targeting its 3′-untranslated region; RhoA upregulated N-cadherin and vimentin levels; however, it downregulated the E-cadherin level. In conclusion, our study showed that miR-1301-3p could serve as a prognostic biomarker for PC and suppress PC cell malignancy by targeting the RhoA-induced EMT process.